Wetting of amorphous and partial crystalline Co73Si10B17 by Sn and Sn-based lead-free solders. (July 2019) - Lin, Qiaoli; Ye, Changsheng; Sui, Ran; Ci, Wenjuan
Abstract: Using wetting balance method, the wetting of Co73 Si10 B17 in amorphous and partial crystalline states by Sn and Sn-based lead-free solders (Sn-0.7Cu and Sn-0.3Ag-0.7Cu) were studied at 290–310 °C. The surface energy of the Co-based alloys was calculated by three methods (Zisman method, Fowkes and Owen theory). Although the calculated surface energy shows the presence of oxide film on the surface of all Co-based alloy, the amorphous Co73 Si10 B17 has a relatively higher surface energy. The wetting mechanism is the oxide film removal, which was caused by a series of complex multiple reactions. The final wettability of Co73 Si10 B17 was affected by the interfacial reaction products and surface oxide film, but was determined by the degree of the oxide film removal. In addition, RMA flux is not very effective for soldering of Co-based alloy whether in amorphous or partial crystalline state owing to its weak activity, especially it is not suitable for soldering of partial crystalline Co73 Si10 B17 . Highlights: Amorphous Co73 Si10 B17 has a better wettability than partial crystalline one. Wetting was caused by the oxide film removal. Relatively higher surface energy of amorphous Co73 Si10 B17 caused the better wettability.